EVALUATION OF GRAPHICAL AND MULTIVARIATE STATISTICAL METHODS FOR CLASSIFICATION OF WATER CHEMISTRY DATA - Guler C.; Thyne G.D.; McCray J.E.; Turner A.K. (My University, 2002)
A robust classification scheme for partitioning water chemistry samples into homogeneous groups is an important tool for the characterization of hydrologic systems. In this paper we test the performance of the many available graphical and statistical methodologies used to classify water samples including: Collins bar diagram, pie diagram, Stiff pattern diagram, Schoeller plot, Piper diagram, Q-mode hierarchical cluster analysis, K-means clustering, principal components analysis, and fuzzy k-means clustering. All the methods are discussed and compared as to their ability to cluster, ease of use, and ease of interpretation. In addition, several issues related to data preparation, database editing, data-gap filling, data screening, and data quality assurance are discussed and a database construction methodology is presented. The use of graphical techniques proved to have limitations compared with the multivariate methods for large data sets. Principal components analysis is useful for data reduction and to assess the continuity/overlap of clusters or clustering/similarities in the data. The most efficient grouping was achieved by statistical clustering techniques. However, these techniques do not provide information on the chemistry of the statistical groups. The combination of graphical and statistical techniques provides a consistent and objective means to classify large numbers of samples while retaining the ease of classic graphical presentations.
Keywords: CLASSIFICATION TECHNIQUES; CLUSTER ANALYSIS; DATABASE CONSTRUCTION; FUZZY K-MEANS CLUSTERING; WATER CHEMISTRY